Existing and emerging treatments for idiopathic pulmonary fibrosis. (4th March 2019) - Kolilekas, Lykourgos; Papiris, Spyridon; Bouros, Demosthenes
ABSTRACT: Introduction : Idiopathic pulmonary fibrosis (IPF) is a progressive and invariable fatal interstitial lung disease. Current antifibrotic treatment halts disease progression but does not cure the disease itself. In the last decade, a substantial understanding of disease pathobiological mechanisms led to the development of numerous clinical trials testing promising pharmacologic agents. Areas covered : In this review, we summarize and discuss current and emerging pharmacological therapies for IPF and highlight the potential of different promising investigational compounds in phase II-IV trials with positive or pending results. Expert commentary : Existing therapies for IPF slow disease progression and recent advances in understanding IPF complex pathogenesis unfolded multiple new possible therapeutic targets. A relevant number of promising clinical trials targeted specific biologic pathways, are ongoing or upcoming, but we are far away from a definitive cure of IPF soon. An 'oncologic approach' via tailoring medicine could be a realistic therapeutic intervention that may improve expectancy and quality of life in IPF.